CARDIAC EXTRASYSTOLE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Extrasystole is an often-benign alteration of the heart rhythm. This is an early pulsation contraction of the heart, which the affected individual can clearly perceive as an abnormal contraction of the organ, an “added” or “irregular” heartbeat compared to the normal heartbeat, but which only instrumental examinations are able to detect and typify accurately.